Teachers of Color & Self-Efficacy in Social and Emotional Learning (SEL): Strengthening Equity-Based Approaches to SEL - White, Terrenda; Bristol, Travis; Britton, Tolani (Urban education (Beverly Hills, Calif.), 2024)
This article examines teacher self-efficacy in social and emotional learning (SEL), particularly by teachers of color, and the conditions that shaped their efficacy beliefs. Data are drawn from surveys with two teacher groups, one comprised of teachers of color and a comparative group that was predominantly white. Surveys were followed by interviews and observations with teachers in each group. Findings showed that teachers of color reported stronger efficacy beliefs in SEL and described practices that centered racial justice. Differences in efficacy are attributed to a social justice learning community that provided efficacy-forming experiences for teachers of color to enact equity-based SEL practices.